Positioning intestinal ultrasound in a UK tertiary centre: significant estimated clinical role and cost savings. Issue 1 (8th July 2022) - Luber, Raphael P; Petri, Bianca; Meade, Susanna; Honap, Sailish; Zeki, Sebastian; Gecse, Krisztina B; Griffin, Nyree; Irving, Peter M
Abstract : Objective: Intestinal ultrasound (IUS) is an inexpensive, non-invasive method of diagnosing and monitoring inflammatory bowel disease (IBD). We aimed to establish the proportion of lower gastrointestinal endoscopies (LGIEs) and magnetic resonance enterographies (MREs) that could have been performed as IUS, the potential pathology miss-rates if IUS was used and the associated cost savings. Methods: All MREs and LGIEs performed for either assessment of IBD activity or investigation of possible IBD, performed at a single UK tertiary centre in January 2018, were retrospectively reviewed against predetermined criteria for IUS suitability. Case outcomes were recorded and cost of investigation if IUS was performed instead was calculated. Results: 73 of 260 LGIEs (28.1%) and 58 of 105 MREs (55.2%) met the criteria for IUS suitability. Among potential IUS-suitable endoscopy patients, one case each of a <5 mm adenoma and sessile serrated lesion were found; no other significant pathology that would be expected to be missed with IUS was encountered. Among IUS-suitable MRE patients, no cases of isolated upper gastrointestinal inflammation likely to be missed by IUS were found, and extraintestinal findings not expected to be seen on IUS were of limited clinical significance. The predicted cost saving over 1 month if IUS was used instead was £8642, £25 866 and £5437 for MRE, colonoscopy and flexible sigmoidoscopy patients, respectively. Conclusion: There is a significant role for IUS, with annual projected cost savings of up to almost £500 000 at our centre. Non-inflammatory or non-gastrointestinal pathology predicted to be missed in this cohort was of limited clinical significance.